DISKRIMINASI GENDER YANG DIALAMI TOKOH TAKAKO OTOMICHI DALAM NOVEL KOGOERU KIBA KARYA ASA NONAMI - Medah, Tiari Christin (Humanis, 2014)
Gender differences have spawned various gender discrimination for both men and particularly to women. Women discrimination can be caused by the view of people who think of women as second class citizens whose existence was not consider so that indirectly have a negative impact on women. Those viewpoints can be derived from a patriarchal culture, a culture which states that men can completely control women. It also occurs in Japanese society, one of which is reflected through the novel Kogoeru Kiba by Asa Nonami. Forms of gender discrimination were experienced by female characters in the novel Kogoeru Kiba, namely Takako Otomichi, among other stereotype, subordination, and psychological violence. Manifestation feminism as an attempt to overcome gender discrimination performed by Takako Otomichi seen from the position in Japanese society, purpose of life, and Takako Otomichi’s attitude.
Keywords: Gender, Discrimination, Feminism